SAT0169 Frequency of Spondyloarthritis in Italian Patients with BehÇEt'S Disease. (23rd January 2014) - Leccese, P.; D'Angelo, S.; Gilio, M.; nigro, A.; Lofrano, M.; Palazzi, C.; Padula, A.; Olivieri, I.
Abstract : Background: Till now the debate on the relationship between Behçet's disease (BD) and spondyloarthritis (SpA) has been limited to whether the frequency of sacroiliitis and ankylosing spondylitis (AS) is greater or not in patients with BD than in controls. But if BD and SpA occur together more frequently than by change, it should be possible to find patients with BD showing different forms of SpA. In actual fact, some patients with BD and undifferentiated SpA were reported in the last two decades. Recently, the Assessment of SpondyloArthritis international Society (ASAS) developed and validated classification criteria for axial and peripheral SpA that are going to substitute the Amor criteria and the European Spondylarthropathy Study Group (ESSG) criteria for all forms of SpA. Objectives: The aim of our study was to evaluate the frequency of Italian patients with BD meeting the ASAS classification criteria for SpA. Methods: Consecutive patients attending the outpatient clinic for BD of the Rheumatology Department of Lucania and meeting the International Study Group (ISG) criteria were assessed. Each patient was asked about the presence of SpA or related diseases, such as psoriasis and inflammatory bowel disease (IBD), in his first-degree relatives. Each patient was evaluated for clinical manifestations of SpA including, inflammatory low back pain, spinal limitation and deformity, peripheral arthritis, peripheral enthesitis, dactylitis and acute anterior uveitis. Pelvic plain films were obtained in all patients and examined blindly and independently for sacroiliac joint changes by two observers. HLA typing was performed by PCR-SSP. Results: During a 6-month period, 74 consecutive patients (49 M, 25 F; mean age 39.8±11.4 yrs; mean disease duration 17.8±8.9 yrs; 64% HLA-B51 positive) with BD were recruited. Seven (9.4%) out of them met the ASAS classification criteria for SpA. Of these, 1 had axial disease with the feature of AS and 6 peripheral SpA. In 2 of these 6, acute anterior uveitis without posterior involvement was essential for the diagnosis of SpA. The remaining 4 had psosiasis, dactylitis, enthesitis or inflammatory chronic low back pain in addition to peripheral arthritis. Two of the 7 patients with SpA features were HLA-B27 positive. Conclusions: Italian patients with BD show a higher frequency of SpA, as defined by the ASAS criteria, than that expected in the general population. Disclosure of Interest: None Declared